The Use of Educational Robots to Engage the Youth in Computer Science: A Case Study - Nusayr, Amjad; Silva, Rogério (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
The use of robotics and robot design programming was viewed to be strictly used in the domain of higher education. Degree programs like computer science, computer engineering, and even mechanical engineering utilize robotics courses to introduce students to the use of robotics in different applications. The advances in engineering and the lowered hardware cost made acquiring and building a robot an easier task for a person to get started in robotic education. That lower cost also made it possible for many organizations across the world to hold educational programs and camps to educate young students in programming and robotics. In this paper we show a case study on how robotic programming camps for teens helped shape their ideas in the computer science field and engage students in programming interest.